65.9k views
3 votes
ABCD is a rhombus. Solve for x, if m AFB
(16x + 6)
B
F
D
C

ABCD is a rhombus. Solve for x, if m AFB (16x + 6) B F D C-example-1

2 Answers

3 votes

The value of x is 6.7°.

Since ABCD is a rhombus, all of its sides are equal. We are given that the diagonals intersect at point E.

We are also given that AE = 23x and EC = x - 10. We need to find the value of x.

From the diagram, we can see that triangle ABE is a right triangle, with angle AEB being a right angle.

We are also given that m/AEB = (16x + 6)°.

Using the Pythagorean Theorem, we can find the length of AB:

AB^2 = AE^2 + EB^2

Since ABCD is a rhombus, we know that AB = AD. Substituting this into the equation, we get:

AD^2 = AE^2 + EB^2

We are given that AE = 23x and EC = x - 10. Substituting these values into the equation, we get:

AD^2 = (23x)^2 + (x - 10)^2

Simplifying the equation, we get:

AD^2 = 529x^2 + 40x - 100

We are also given that m/AFB = (16x + 6)°. Since ABCD is a rhombus, we know that AFB = 90°. Substituting this into the equation, we get:

m/AEB = 180° - m/AFB

m/AEB = 180° - (16x + 6)°

m/AEB = 174° - 16x

Since triangle AEB is a right triangle, we know that the sum of the angles in the triangle is 180°. Therefore, we can write the following equation:

m/AEB + m/ABE + m/BAE = 180°

Substituting the values we know, we get:

174° - 16x + m/ABE + m/BAE = 180°

Combining like terms, we get:

m/ABE + m/BAE = 6x + 6°

Since diagonals of a rhombus bisect opposite angles, we know that m/ABE = m/BAE. Therefore, we can rewrite the equation as:

2 * m/ABE = 6x + 6°

m/ABE = 3x + 3°

We also know that m/AEB = 90° - m/ABE. Substituting the value we found for m/ABE, we get:

m/AEB = 90° - (3x + 3°)

m/AEB = 87° - 3x

Now we can set the two expressions for m/AEB equal to each other:

87° - 3x = 174° - 16x

Solving for x, we get:

13x = 87°

x = 6.7°

Therefore, the value of x is 6.7°.

User Wilson Vargas
by
5.0k points
4 votes
2(8x+3) all you need to do is apply
User Daxon
by
4.2k points